Virtual Reality Analgesia During Venipuncture in Pediatric Patients With Onco-Hematological Diseases - Atzori, Barbara; Hoffman, Hunter G.; Vagnoli, Laura; Patterson, David R.; Alhalabi, Wadee; Messeri, Andrea; Lauro Grotto, Rosapia (Frontiers in Psychology, 2018)
Abstract Background. Venipuncture is described by children as one of the most painful and frightening medical procedures. Objective. To evaluate the effectiveness of Virtual Reality (VR) as a distraction technique to control pain in children and adolescents undergoing venipuncture. Methods. Using a within-subjects design, fifteen patients (mean age 10.92, SD = 2.64) suffering from oncological or hematological diseases received one venipuncture with “No VR” and one venipuncture with “Yes VR” in two separate days (treatment order randomized). “Worst pain”, “Pain unpleasantness”, “Time spent thinking about pain”, the quality of VR experience, fun and nausea were measured. Results. During VR, patients reported significant reductions in “Time spent thinking about pain”, “Pain unpleasantness” and “Worst pain”. Patients also reported significantly more of fun during and reported a “Strong sense of going inside the computer-generated world” during VR. No side effects were reported Conclusions. VR can be considered an effective distraction technique for children and adolescents’ pain management during venipuncture. Moreover, VR may elicit positive emotions, more than traditional distraction techniques. This could help patients cope with venipuncture in a non-stressful manner. Additional research and development is needed.